TEMPE KORO PEDANG (Canavalia ensiformis [L.] DC) DITINJAU DARI SIFAT FISIK DAN KIMIA - Christiana, Retnaningsih; Sumardi, Sumardi; Adytyas, Sunjaya (Seri Kajian Ilmiah, 2014)
Jack beans (Canavalia ensiformis [L.]DC) are legume that rich in protein content (23,8â27,6% in dry bean). In Indonesia, people seldom use it for daily consumption. Therefore, needed some ways to make this more usefull. One of the ways is used as raw material in tempe production. Processing known can change the composition of foodstuff compounds. In tempe production, there are many step of processing that important, but in this study focus just on soaking process. The goal of this research is to know effect of soaking (during 24 hours, 36 hours and 48 hours) on physicochemical properties of jack bean tempe. Results show that increasingly the time of soaking make hardness reduction, influence the proximate composition especially reduce protein and ash (mineral) content. Tempe which have the higest value of hardness is tempe with 24 hours soaking (1645,74 gf). The 24 hours soaking tempe have 62,78 % moisture, 2,93 % ash, 20,48 % crude protein, 1,86 % lipid, and 11.95 % carbohidrate content. The 36 hours soaking tempe have 61,82 % moisture, 2,39 % ash, 19,76 % crude protein, 2,25 % lipid, and 13.78 % carbohidrate content. The 48 hours soaking tempe have 61,84 % moisture, 1,92 % ash, 18,87 % crude protein, 2,57 % lipid, 2,82 % crude fiber, and 14.81 % carohidrate content.